Cognitive Training in Patients with Alzheimer's Disease: Findings of a 12-month Randomized Controlled Trial - Trebbastoni, Alessandro; Imbriano, Letizia; Podda, Livia; Rendace, Lidia; Sacchetti, Maria L.; Campanelli, Alessandra; D'Antonio, Fabrizia; de Lena, Carlo (Current Alzheimer Research, 2018)
Background: Cognitive training (CT) is a non-pharmacological intervention based on a set of tasks that reflect specific cognitive functions. CT is aimed at improving cognition in patients with cognitive impairment, though no definitive conclusions have yet been drawn on its efficacy in Alzheimer's disease (AD). Objective: To assess the effectiveness of a CT program designed to improve cognition in AD patients. Method: This is a randomized, controlled, single-blind, longitudinal trial with a no-treatment control condition in mild-to-moderate AD. Treated patients received in-group CT twice a week for six months, whereas controls did not. CT consisted of tasks ranging from paper-and-pencil to verbal-learning exercises. Participants' cognitive levels were assessed at baseline, post-intervention and 6 months later by means of a complete neuropsychological test battery. Repeated measures ANOVA was used to analyze the effect of time on the outcome measures, as well as to compare treated and untreated patients over time, with demographic data considered as covariates. Results: Of the 140 patients enrolled, 45 in the treated group and 85 controls concluded the study. The CT significantly improved treated subjects' cognitive functions immediately after the CT. Six months later, some test scores remained stable when compared with those obtained at baseline. The control group performed significantly worse than the treated group at each time-point, displaying a progressive cognitive decline over time. Conclusion: Our results suggest that CT may improve cognitive functions in patients with AD and may help to temporarily slow their cognitive decline.
Keywords: non-pharmacological intervention